Stress analysis and fatigue life prediction of a wobble plate - Tamin, Mohd. Nasir (2007)
A five-stage compressor for compressing natural gas is being designed and evaluated. The compressor operates at 1500 rpm with natural gas pressure of 50 psi. This study examines deformation behavior, stress and strain distribution of the wobble plate component of the compressor. Fatigue loading on the wobble plate is computed from the reaction of compressed gas in each of the five cylinders. The highest pressure in the 5th cylinder is 3000 psi. The calculated stress evolution per revolution of the wobble plate is utilized to predict the fatigue lives of the wobble plate. The fatigue life prediction is performed using Brown-Miller algorithm with Morrow mean stress correction method. Results show that the stress is concentrated in the vicinity of the contact region between the guide plate and the polymer guide ball. The highest stress in the wobble plate and the polymer guide ball is 160.4 MPa and 127.8 MPa respectively. The corresponding predicted fatigue life of the wobble plate is 8x108 cycles. A higher stress gradient in the guide ball (max von Mises stress is 3.3 GPa) is predicted when a harder steel ball is employed. This is due to high stiffness of the mating plate/ball surfaces.